Initial experience with the new ethylene vinyl alcohol copolymer based liquid embolic agent Menox in the endovascular treatment of cerebral arteriovenous malformations. (30th May 2019) - Sirakov, Stanimir; Sirakov, Alexander; Minkin, Krasimir; Penkov, Marin; Ninov, Kristian; Hristov, Hristo; Karakostov, Vasil; Raychev, Radoslav
Abstract : Background and Purpose: Liquid embolic agents (LEAs) are the determinant tool for successful embolization of cranial arteriovenous shunts. There are few currently available LEAs. The aim of the study was to summarize our initial experience with a recently introduced non-adhesive ethylene vinyl alcohol (EVOH) copolymer based LEA (Menox 18) in the endovascular treatment of cerebral arteriovenous malformations. Methods: From April 2018 to November 2018, 24 patients harboring cerebral arteriovenous malformations underwent endovascular embolization with Menox 18. Clinical features, angiographic results, procedural details, complications, and follow-up details were prospectively collected and retrospectively analyzed. Results: Curative embolization in one endovascular session was achieved in 14/24 (58.3%) of the treated patients. Partial embolization was achieved in 10 patients (42.6%) in whom staged treatment with radiosurgery or microsurgical resection was planned. No mortality was recorded in our series. Clinical complications after embolization occurred in 1/24 (4.66%) patients. No technical complications were noted Conclusions: Our pilot study suggests that the Menox embolization system offers similar technical and clinical results in comparison with the other currently available LEAs. Further studies with larger cohorts and long term follow-up data are needed to fully evaluate its efficacy